MANAGEMENT OF CHILLI POWDERY MILDEW CAUSED BY LEVEILLULA TAURICA (LEV.) ARN. USING FUNGICIDES AND BIOPESTICIDES (Journal of Plant Disease Sciences, 2025)
Chilli powdery mildew caused by is one of the most serious disease of chilli. Field experiment was carried out to know the effect of different fungicides and biopesticides against powdery mildew of chilli during 2024–25.Among the fifteen treatments, Myclobutanil 10% WP (1g/l) emerged as the most effective treatment, recording the lowest PDI (16.91%) and highest yield (135.32 q/ha), with a highest cost- benefit ratio of 1:3.30. Sprays of Azoxystrobin 23% SC and Kresoxim-methyl 44.3% SC also exhibited significant disease reduction and yield improvement. Among biopesticides, was identified as the most effective, although not as effective as Ampelomyces quisqualis synthetic fungicides. The research emphasizes Myclobutanil as the most cost-effective choice for managing powdery mildew in chilli, whereas biopesticides provide safer but less effective alternatives.
Keywords: Ampelomyces quisqualis Chilli, Disease, Powdery mildew, Myclobutanil,